2023
DOI: 10.1111/jdv.19167
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of scabies worldwide—An updated systematic literature review in 2022

Abstract: Scabies is a World Health Organization‐defined neglected tropical disease, with continuously rising incidence worldwide in recent years. The aim of this study was to provide an update of the worldwide prevalence and new treatment approaches of scabies in population‐based settings. MEDLINE (PubMed), Embase and LILACS databases were reviewed for English and German language population‐based studies from October 2014 to March 2022. Two authors independently screened the records for eligibility, extracted all data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 58 publications
2
11
0
Order By: Relevance
“…The findings of our study are consistent since this study also noted a significantly higher burden of scabies in the Pacific region in comparison to the other regions. Another recent meta-analysis [77] reported a very wide range of scabies prevalence from 0.18% to 79.6% as did the study by Romani which had a range from 0.2% to 71.4% [76]. The pooled prevalence in our study is similar with a 95% pooled confidence interval spanning 1.4% and 71%.…”
Section: Strengths and Weaknesses In Relation To Other Studies Discus...supporting
confidence: 84%
“…The findings of our study are consistent since this study also noted a significantly higher burden of scabies in the Pacific region in comparison to the other regions. Another recent meta-analysis [77] reported a very wide range of scabies prevalence from 0.18% to 79.6% as did the study by Romani which had a range from 0.2% to 71.4% [76]. The pooled prevalence in our study is similar with a 95% pooled confidence interval spanning 1.4% and 71%.…”
Section: Strengths and Weaknesses In Relation To Other Studies Discus...supporting
confidence: 84%
“…The national population-based survey prevalence in our review (2.75%) was lower than Australia (4.2%), the country with the lowest prevalence among general population-based studies in a 2023 systematic review on prevalence studies worldwide. 7 However, there are institutions (orphanages and aged care homes) and settings (tertiary hospital dermatology clinics) that still showed high prevalence in the Philippines.…”
Section: Discussionmentioning
confidence: 99%
“…The highest prevalence in our study were children 0 to 14 y/o, which was also found in a 2023 systematic review where 5 of the 43 included studies collected age-specific data and showed higher prevalence among children < 20 y/o than those > 20 y/o (Fiji Islands, Liberia, Solomon Islands, Vanuatu). 7 Children have relatively thinner skin and are more susceptible to infestation by scabies mites. In addition, children are more physically active and may have frequent skin-to-skin contact when playing or interacting in the school and community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The systematic literature review on the worldwide scabies prevalence by Schneider et al 4 provides a comprehensive and welcome update on the only previous systematic review on the subject published in The Lancet in 2015. 5 At the same time, limitations and shortcomings of such data are evident.…”
mentioning
confidence: 99%